2006
DOI: 10.1111/j.1479-828x.2006.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

A medical management of interstitial ectopic pregnancy: A 5‐year clinical study

Abstract: The methotrexate/folinic acid regimen used as a one-dose treatment is safe and effective for unruptured interstitial pregnancy, with no side-effects and the advantage of avoiding invasive surgery. Subsequent tubal patency and reproductive function are yet to be ascertained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 14 publications
3
61
0
3
Order By: Relevance
“…The mean duration of undetectable HCG in serum is 43 +/-64 days (Jourdain et al, 2003). An interstitial mass or heterogeneous area with persistent vascularization on ultrasound has been reported (Tang et al, 2006). Subject to negativity complete of HCG, they do not constitute a therapeutic failure (Tang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The mean duration of undetectable HCG in serum is 43 +/-64 days (Jourdain et al, 2003). An interstitial mass or heterogeneous area with persistent vascularization on ultrasound has been reported (Tang et al, 2006). Subject to negativity complete of HCG, they do not constitute a therapeutic failure (Tang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial ectopic pregnancies, also called cornual pregnancies occur in 1-4% of ectopic gestations [1]. Risk factors include ipsilateral ectopic pregnancy, salpingectomy and in vitro fertilization [2].…”
Section: Introductionmentioning
confidence: 99%
“…Serially repeated transvaginal ultrasonographic examinations are not necessary, since the differences that can be detected in such examinations are not indicative of, or able to predict, treatment failure. 18,19 Nevertheless, the evidence of embryonic cardiac activity one week after the initial treatment, despite a significant decrease in serum β-hCG levels, showed that one follow-up transvaginal ultrasonographic examination was indispensable in our case.…”
mentioning
confidence: 99%
“…This treatment has the advantages of generally being highly effective, not causing any side effects and avoiding possible complications associated with a surgical procedure. 18 One week after the initial dose, the patient's serum β-hCG concentration had decreased by over 15%, which is considered to be sufficient decline on the seventh day after treatment. 7 Nevertheless, transvaginal ultrasonography examination detected an embryo with cardiac activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation